KOMPOSISI JENIS DAN KEANEKARAGAMAN FITOPLANKTON SAAT PENAMBANGAN PASIR INTENSIF DI MUARA SUNGAI POHARA SULAWESI TENGGARA - Bahtiar N. Irawati (Universitas Mataram, 2013)
AbstractLocal communities along the banks of Pohara River have been benefited from the ecologicalservices provided by the river ecosystem. However, the increasing trend of extraction patternof natural resources through several economic activities along the river has put significantpressure on the surrounding ecosystem. One of the activities that allegedly have an impact onthe estuary productivity decline of the area is intensive sand mining operations. This recentstudy was carried out to study the composition and diversity of phytoplankton during heavysand mining season in order to provide baseline data for the better management of the area.Field work was conducted from April 2007 to February 2008 in Pohara estuary. Planktonsamples were collected from six sampling stations and analyzed using quantitative descriptivemethod. Results of the study found that the highest spatial and temporal distribution ofphytoplankton species found in the areas were phytoplankton from the classes ofChlorophyceae and Dinophyceae while the lowest was from the class of Euglenophyceae.Two species found in every sampling station were Euglenophyceae and Cyanophyceae.Diversity index showed significant differences and categorized from high to low diversitybased on sampling stations and observation times with the values ranged between 2231-2524and 0906-2346, respectively. In addition, the uniformity index based on station andobservation times ranged between 0758-0819 and 0906-2346, respectively which fell in thecategory of high and medium uniformity.Keywords : Phytoplankton, Composition, Diversity, Pohara RiverÃÂ